Modern methods of fixation at traumatic damages of сranio-vertebral junction, results of operative intervention - Polishchuk, M. E.; Slynko, E. I.; Buryk, V. M.; Pastushin, A. I.; Verbov, V. V. (Ukrainian Neurosurgical Journal)
The results of 11 patients treatment in with traumatic damage CVJ for the period of 2001 for 2003 with application of modern fixing systems were analysed. At 8 patients occipitocervical stabilization in various updatings has been carried out, 3 patients were operated with the use of anterior methods (2 — transoral removal of dens СII, with the subsequent stabilization, and 1 — transdental screw fixing dens СII). During the remote postoperative period at all patients are defined formations of a bone callous and absence of secondary instability CVJ. The peculiarity of operative technique and technical equipment are considered at installation of various kinds of modern fixing systems. The conclusion about significant improvement of results of treatment of traumatic instability CVJ is made at application of modern fixing systems.